OSS Adoption: Who is Leading and Why? - Daniel Nepelski; Sushmita Swaminathan (Weekly Report, 2007)
Parallelsacht. "OSS Adaption" war Hauptsachtitel der 1. Version, die 14 Tage lang im Netz stand. It is no secret that open source software (OSS) is gaining ground, yet the drivers for OSS adoption still seem rather unclear. This report aims to compare various industries within select countries in the EU and tries to explain their OSS adoption patterns. The results indicate that companies in Poland, the Czech Republic and Hungary are leading OSS adopters. Further, it was found that company adoption of OSS is largely dependent on in-house IT development and expertise. The focus on internal development and capacities is often characteristic of larger firms, which is corroborated by our findings. Finally, the analysis showed that companies tend to OSS, the higher their requirements for open standards and interoperability.
Keywords: L86; O33; O52; D21; 330; Open source software; Adoption: Internal IT capacity; User innovation